Rasio Leverage dan Aktivitas dalam Mempengaruhi Profitabilitas Perusahaan Farmasi - Hidayat, Taufik; Dasman, Sunita; Oktaviano, Benny; Wahyuningsih, Mesela Nurhana (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This study aims to analyse the effect of Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on Return on Equity (ROE) in the context of corporate financial performance. DAR measures the extent to which the company's assets are financed with debt, DER measures the company's capital structure, while TAT measures how efficient the company is in generating revenue from its assets. ROE is a metric that reflects a company's level of profitability compared to shareholders' equity. This study uses a quantitative approach in which the data is in the form of annual financial reports of Pharmaceutical Companies for the period 2017 - 2021. This study aims to determine, examine and analyse the conditions of Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on Return on Equity (ROE). The sampling technique used purposive sampling. This type of research uses quantitative descriptive analysis with data analysis techniques using panel data regression analysis. The results showed that DAR and TATO had a significant positive effect on ROE, while DER did not affect ROE. From the research results, the company should pay more attention to capital and asset turnover to be more effective in increasing profits.